VOLATILE ORGANIC COMPOUNDS FROM AUTOMOBILE AND LIGHT DUTY TRUCK MANUFACTURING: A REVIEW OF BEST PRACTICES TO MEET REGULATORY REQUIREMENTS - Yates, Douglas M. (My University, 2005)
Smog events continue to occur in Southern Ontario and maximum ground level ozone concentrations exceed the Canada Wide Standard (CWS). Ontario’s automotive manufacturing sector, while perceived as a significant contributor to volatile organic compounds (VOC) emissions (an ozone precursor) at 10 kt per year, contributes only 1.5% of Ontario’s 649 kt annual emissions. Canada’s current VOC guideline for automotive surface coating for new facilities at 55 g/m2 is higher than Europe’s new standard at 45 g/m2 or Germany’s at 35 g/m2. However, Canada’s VOC guideline for automotive surface coating for existing facilities at 55 g/m2 is lower than Europe’s standard at 60 g/m2. Canadian auto manufacturers have made significant reductions since the early 1990’s and are now achieving VOC emissions on average of approximately 36 g/m2. General Motors (GM) new paint shop for its Oshawa Car Plant is expected to achieve VOC emissions of approximately 15 g/m2 in 2006. Therefore, it can be concluded that through a combination of voluntary (Ontario’s Anti Smog Action Plan - ASAP), regulatory (air permitting) and corporate initiatives (emission reduction objectives and common paint shop designs), Ontario’s automotive manufacturers are achieving VOC emission performance found in the most stringent European jurisdiction (Germany), and with new installations (i.e. GM Oshawa Car) will approach the performance of US Environmental Protection Agency (EPA) Best Available Control Technology (BACT) standards. Considering the above, it is recommended that the Ontario Ministry of the Environment should continue with its current approach of using the ASAP program and air permitting to control VOC emissions from Ontario’s automotive manufacturers. It is also recommended that the Ministry of the Environment consider, in consultation and cooperation with the Canadian Council of Ministers of the Environment (CCME) and the automotive manufacturing sector in Ontario, updating the New Source Performance Standards and Guidelines for the Reduction of VOC Emissions from Canadian Automotive Original Equipment Manufacturers (OEM) Coating Facilities to reflect the current performance of the Ontario automotive manufacturing sector.
VOLATILE ORGANIC COMPOUNDS FROM AUTOMOTIVE MANUFACTURING
Keywords: Automobile manufacturing; Volatile organic compounds; Southern Ontario; Emissions; VOC